Study on the Absorption and Immunity Regulation of Simulated Breast Milk Nutrients in Rats - Xie, Qinggang; Zhang, Jinlan; Liu, Yang; Yang, Yi; Wei, Yanli; Jiang, Shilong; Cui, Dongying; Zhou, Qile (Frontiers in Nutrition, 2022)
Since infant formula (IF) manufacturers aim to produce a product as close to breast milk as possible, fortified nutrients are usually added. Generally, an IF is produced by adjusting the types and proportions of vitamins and minerals. This study comparatively examined the content of the six nutrients in different compound forms in vivo and evaluated the effect of different nutrient pack groups on immunity and growth. The results indicated that the simulated-human milk nutrients (minerals zinc (Zn), iron (Fe), calcium (Ca), and vitamins A, E, and B1) were more easily absorbed by the body while effectively regulating immunity. This study provides a scientific foundation for developing, manufacturing, and applying imitation-breast formula milk powder.